2019
DOI: 10.1021/acs.jpca.9b09423
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization of C60: Effects of Correlation on Cross Sections and Angular Distributions of Valence Subshells

Abstract: Calculations of the photoionization cross section and asymmetry parameter, β, are performed at the density functional theory (DFT) and time-dependent density functional theory (TDDFT) levels for all 32 valence levels of C 60 . Accurate numerical results are obtained for the isolated molecule in icosahedral symmetry. A detailed analysis based on the comparison between the DFT and TDDFT results allows the identification of four types of resonances: the well-known confinement resonances of mainly geometrical orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Both bands suggest the presence of shape resonances above the ionization threshold, around 1-3 eV KE. 65,82 The partial cross sections of the first two bands have been previously calculated by Colavita et al 30 and more recently by Ponzi et al 65 The shapes differ quite significantly (see Fig. 9) and they, furthermore, do not account for all the shape resonances that are evident in our measurement.…”
Section: Absolute Photoionization Cross Section Around the Lyman-a Limitmentioning
confidence: 51%
See 3 more Smart Citations
“…Both bands suggest the presence of shape resonances above the ionization threshold, around 1-3 eV KE. 65,82 The partial cross sections of the first two bands have been previously calculated by Colavita et al 30 and more recently by Ponzi et al 65 The shapes differ quite significantly (see Fig. 9) and they, furthermore, do not account for all the shape resonances that are evident in our measurement.…”
Section: Absolute Photoionization Cross Section Around the Lyman-a Limitmentioning
confidence: 51%
“…theoretically obtained values. 65,82 The recent results from Ponzi et al 65 predict a much more negative value of b for the HOMO 6h u band for slow photoelectrons (KE o 4 eV), while the agreement for faster photoelectrons is more reasonable. As for the second band, the calculations predict negative anisotropy values ranging from À0.7 to À0.1 for both 6g g and 10h g states in our photon energy range, while our experimental values start at À0.5 at 10.5 eV and progress towards slightly positive values at 13.5 eV.…”
Section: Threshold Photoelectron Spectrum (Tpes)mentioning
confidence: 96%
See 2 more Smart Citations
“…Photoionization of C has been investigated several times [ 34 , 35 , 36 , 37 ]. Illustrative results from recent studies are reported in Figure 2 .…”
Section: Applicationsmentioning
confidence: 99%